Oral Rehydration on Infants and Children in the Dr. Hasan Sadikin General Hospital, Bandung - Djoeanda P; Wyati Donhuijsen (Indonesian Pediatric Society, 1979)
Fifty-nine out of one hundred and fifty-jour patients with gastroenteritis and dehydration admitted between April and September 1975 to the Department of Child Health, Dr. Hasan Sadikin General Hospital, were treated with oral glucose electrolyte solution and studied.Twenty-nine patients (group I) were treated with P.3.M. formula and thirty patients (group II) with Hirschhorn formula. In both groups no significant differences were noted in grades of volume depletion which ranged between 5 to 10%, with a peak incidence of 8%. Rehydration was excellent in 41 (69.6%), good in 14 (23.7%) and poor in 4 patients (6.7%). No significant differences were found between both groups. The mean weight gain after rehydration was 4.5% (of the initial weight) in group I and 4.49% in group II (no significant differences). In the study of Hirchhorn et al. (1975) the mean weight gain was about 3%. Fifty-four patients (91.5%) had a recognized pathogen in their stool. In general, the result of oral rehydration in this study was satisfactory; statistically the treatment with both oral glucose electrolyte solutions gave the same good results.